3D‐QSAR and scaffold hopping based designing of benzo[d]ox‐azol‐2(3H)‐one and 2‐oxazolo[4, 5‐b]pyridin‐2(3H)‐one derivatives as selective aldehyde dehydrogenase 1A1 inhibitors: Synthesis and biological evaluation. Issue 9 (26th May 2022) - Verma, Himanshu; Narendra, Gera; Raju, Baddipadige; Kumar, Manoj; Jain, Subheet K.; Tung, Gurleen K.; Singh, Pankaj K.; Silakari, Om
Abstract: Aldehyde dehydrogenase 1 (ALDH1A1), an oxidoreductase class of enzymes, is overexpressed in various types of cancer cell lines and is the major cause of resistance to the Food and Drug Administration (FDA)‐approved drug, cyclophosphamide (CP). In cancer conditions, CP undergoes a sequence of biotransformations to form an active metabolite, aldophosphamide, which further biotransforms to its putative cytotoxic metabolite, phosphoramide mustard. However, in resistant cancer conditions, aldophosphamide is converted into its inactive metabolite, carboxyphosphamide, via oxidation with ALDH1A1. Herein, to address the issue of ALDH1A1 mediated CP resistance, we report a series of benzo[ d ]oxazol‐2(3 H )‐one and 2‐oxazolo[4, 5‐ b ]pyridin‐2(3 H )‐one derivatives as selective ALDH1A1 inhibitors. These inhibitors were designed using a validated 3D‐quantitative structure activity relationship (3D‐QSAR) model coupled with scaffold hopping. The 3D‐QSAR model was developed using reported indole‐2, 3‐diones based ALDH1A1 inhibitors, which provided field points in terms of electrostatic, van der Waals and hydrophobic potentials required for selectively inhibiting ALDH1A1. The most selective indole‐2, 3‐diones‐based compound, that is, cmp 3, was further considered for scaffold hopping. Two top‐ranked bioisosteres, that is, benzo[ d ]oxazol‐2(3 H )‐one and 2‐oxazolo[4, 5‐ b ]pyridin‐2(3 H )‐one, were selected for designing new inhibitors by considering the field pattern of 3D‐QSAR. All designed molecules were mapped perfectly on the 3D‐QSAR model and found to be predictive with good inhibitory potency (pIC50 range: 7.5–6.8). Molecular docking was carried out for each designed molecule to identify key interactions that are required for ALDH1A1 inhibition and to authenticate the 3D‐QSAR result. The top five inhibitor‐ALDH1A1 complexes were also submitted for molecular dynamics simulations to access their stability. In vitro enzyme assays of 21 compounds suggested that these compounds are selective toward ALDH1A1 over the other two isoforms, that is,  ALDH2 and ALDH3A1. All the compounds were found to be at least three and two times more selective toward ALDH1A1 over ALDH2 and ALDH3A1, respectively. All the compounds showed an IC50 value in the range of 0.02–0.80 μM, which indicates the potential for these to be developed as adjuvant therapy for CP resistance. Abstract : A series of benzo[ d ]oxazol‐2(3 H )‐one and 2‐oxazolo[4, 5‐ b ]pyridin‐2(3 H )‐one derivatives were designed as selective aldehyde dehydrogenase 1 (ALDH1A1) inhibitors, using a validated 3D‐QSAR model coupled with scaffold hopping. All compounds were found to be at least 2–3 times more selective toward ALDH1A1 than ALDH2 and ALDH3A1. Based on their IC50 values, all the compounds showed the potential to be developed as adjuvant therapy for cyclophosphamide resistance.